Chorion biopsy in mongrel dogs - Ferreira,Guilherme J. (2009)
With the great development of the gestational studies in all of the species, we noticed the necessity of adaptations of these techniques for prenatal diagnosis in dogs. Based on this, we studied the feasibility of chorion biopsy guided by ultrasound. Our results demonstrated accuracy on the sex determination being 2 males and 12 females, as well as it would be possible to identify chromosome alteration due to the quality of samplings. Sex determination was accomplished with the identification of Y gene chromosomes in PCR technique. After the collection, fragments were prepared for light microscopy studies and revealed fetal chorion tissue, blood colloid and erythrocyte. In the whole material we found hemosiderin impregnations due to the hemolysis and to the residue of blood of the placental marginal hematomes. The submitted female dogs to this technique demonstrated normal puppy births without death.